Minority ethnic pupils in the Longitudinal Study of Young People in England. DCSF Research Report RR-002 - Strand, S (Department for Children, Schools and Families, 2007)
There has been concern for some time about the educational attainment and progress of children from minority ethnic groups in the UK. Recent analyses of national test data by the Department for Education and Skills (DfES)1 reveal continuing low attainment by several minority ethnic groups (DfES, 2006). However the national datasets do not contain wide and rich contextual data to help interpret these results, such as information on pupil attitudes or family circumstances. In 2004 the DfES Longitudinal Study of Young People in England (LSYPE) interviewed a nationally representative sample of over 15,000 young people in Year 9 of school (i.e. those aged 13 or 14 years). The study also interviewed their parents/guardians about their involvement in their children’s education. The study collected information on a wide range of topics and presents a unique insight into the experiences, attitudes and opinions of young people with regards to their school, their education and their choices and aspirations for the future. The primary aim of this analysis of the LSYPE data was to focus on the relationships between various pupil, family, school and neighbourhood factors in order to better understand the reasons for differences in the educational attainment of different ethnic groups.